THE EFFECT OF NONPHARMACOLOGICAL PAIN MANAGEMENT (BEHAVIORAL INTERVENTION) ON ANXIETY AND CRYING TIME IN PRESCHOOLERS DURING INVASIVE PROCEDURES AT RSI JEMURSARI SURABAYA - Wesiana Heris Santy; Nabila Rizqi Syahrizal; Yurike Septianingrum; M. Shodiq (Nurse and Holistic Care, 2026)
Background: Preschool children often experience high anxiety during invasive procedures, which may lead to refusal, prolonged crying, and the risk of psychological trauma. Behavioral interventions are nonpharmacological strategies aimed at reducing these negative responses. Purpose: To determine the effectiveness of behavioral intervention in reducing anxiety levels and crying duration among preschool children undergoing invasive procedures. Methods: A quasi-experimental study with a post-test control group design was conducted among 80 preschool children aged 3–6 years undergoing intravenous cannulation at RSI Jemursari Surabaya. Participants were randomly assigned to an intervention group (n = 40) and a control group (n = 40). The intervention group received behavioral intervention, while the control group received standard care. Anxiety levels were measured using the Face Anxiety Scale, and crying duration was recorded using a stopwatch. Data were analyzed using the Mann–Whitney U test. Results: The intervention group showed significantly lower anxiety levels and shorter crying duration compared to the control group. The mean anxiety score in the intervention group was 1.53, while the control group scored 3.03. The mean crying duration was 47.83 seconds in the intervention group and 138.25 seconds in the control group, indicating the effectiveness of behavioral intervention. Conclusion: Behavioral intervention effectively reduces anxiety and crying duration in preschool children during invasive procedures. This intervention supports holistic nursing care by addressing psychological and emotional needs. Nurses are encouraged to routinely apply behavioral interventions with parental involvement to promote child-centered care.